Culinary Business Management Based on Local Wisdom (Case Study On The Three Mango Tuna Shredded Fish Business) - Rahmawati, Rahmawati; Rakib, Muhammad; Syam, Agus (PINISI Discretion Review, 2023)
This research aims to reveal problems regarding the management of culinary businesses based on local wisdom (Case Study Of the Triple Mango Tuna Fish Floss Business). This research is a type of qualitative descriptive research, that provides an overview and description of the business managamenet implemented by the triple mango tuna fish floss business. Data collection techniques in this research were carried out by means of documentation, observation and interviews. The results of the analysis in the research show that appropriate business management that can be applied to the tuna floss business to support aggressive management is to use management that is oriented towards business development.